Dialect Contact And Phonological Change - Cotter, William (My University, 2020)
This chapter examines phonological and phonetic changes that have been documented and analyzed in spoken Arabic varieties, occurring as a result of dialect contact. The factors contributing to dialect contact in Arabic-speaking communities vary, from economic migration which has encouraged individuals to move into new dialect areas seeking work, to migration that stems from political violence and upheaval. These diverse factors have contributed to the large-scale migration of Arabic speakers to other parts of the Arabic speaking world. As a result, dialect contact is rampant, and decades of Arabic sociolinguistic research have shown that the phonological and phonetic effects of these contact situations have been quite profound.
Keywords: phonological change; HUMANITIES and RELIGION::Languages and linguistics::Other languages::Arabic language; Dialect contact